Juegos recreativos en el desarrollo de la motricidad gruesa en estudiantes de Cuarto año de Educación General Básica paralelo “B” de la Unidad Educativa Adolfo Valarezo, 2023-2024 - Torres Espinoza, Yesmani Ramiro (2025)
This research project is based on the need to strengthen physical skills from an early age, as they play a crucial role in the appropriate physical and emotional development of individuals. Therefore, the main objective is proposed to enhance the application of recreational games in the development of gross motor skills among fourth-grade students enrolled in parallel “B” of Adolfo Valarezo High School. In order to achieve this objective, a mixed-method approach is employed, which included a quasi-experimental design and a correlational analysis. The main methods employed are the inductive and deductive approaches, followed by pre- and post-test instruments, which are guided by five dimensions of gross motor skills and applied to 28 students. Among the main results of the pre-test, it was observed that 39.90% of children encountered challenges with gross motor skills, particularly notable in the dimensions of coordination, balance, agility, speed, and object control. Once these results are analyzed, a program of recreational games is proposed to develop the gross motor skills of children. After the implementation of the program, a notable improvement in the development of gross motor skills among the participants is observed, with a high percentage (96.35%). This indicates that these types of activities promote the development of Physical Education classes. It is essential for teachers to employ various strategies that encourage students to actively participate, thus preventing academic issues derived from deficiencies in motor skills